Epidemiological modeling and Statistical methods - Abstracts of Oral Presentations - Editor, The (Nepal Journal of Epidemiology, 2014)
Abstracts of the Oral Presentations at the session on Epidemiological modeling and Statistical methods at the International Conference on Research Methodology and Research Writing (ICRMSW) 2013. DOI: http://dx.doi.org/10.3126/nje.v4i2.10177